"You have to be clean:" a qualitative study of pubic hair grooming behaviours among women living in Italy. Issue 5 (4th May 2021) - DeMaria, Andrea L.; Rivera, Sydney; Meier, Stephanie; Wakefield, Audrey L.; Long, Laura F.; Miller, Alyssa R.
Abstract: The majority of pubic hair and genital self-image research describes women living in the USA, UK and Australia. This may leave attitudes and behaviours across other cultures and geographic regions ambiguous. The purpose of this study was to describe pubic hair removal attitudes and behaviours among reproductive-age women living in Italy. Individual interviews were conducted with 46 women aged 18-45 years between June and July 2017, living in Florence, Italy and currently utilising the Italian healthcare system. Pubic hair removal was popular among participants. Women mainly removed pubic hair by waxing. Sexual partners influenced removal, as did cultural norms and the desire for cleanliness. Most participants indicated pubic hair removal onset during adolescence, often upon puberty. However, most participants had never discussed removal complications with providers. Pubic hair removal often related to a more positive genital self-image because of social norms surrounding hairlessness. Removal among this sample appears to differ from the literature in other contexts, with women living in Italy engaging in more frequent and earlier waxing. Findings offer opportunities for clinicians to proactively address safe pubic hair practices and women's genital concerns during consultations.